Pengembangan Pembelajaran Atletik pada Sekolah Dasar Kelas V - Siskariyanti; Tria Muhamad Aris (Universitas Insan Budi Utomo, 2024)
This research aims to develop athletic learning based on grade V Elementary School. Games can be structured in a lesson so that it makes it easier for children to play while learning. In addition to learning while playing, students can also develop mentally and physically, because playing is a process of playing and developing high spirituality. Data were collected, namely two physical education learning experts, small group trials of 10 participants and large group trials of 30 participants, and data obtained from questionnaires. The development of athletic learning with games is more emphasized on the actual basic motions of athletics but learning can be used as an athletic learning medium.